Permanence for a Discrete Model with Feedback Control and Delay - Yong-Hong Fan; Lin-Lin Wang (Discrete Dynamics in Nature and Society)
The permanence of a single-species population discrete model with feedback control is considered. We found that if we use the method of comparison theorem, then the additional condition, to some extent, is necessary. But for the system itself, this condition may not be necessary. Here, we use new methods instead of the comparison theorem to get the permanence of the system in consideration; the additional condition in Chen's paper (2007) is deleted.